FORMULATION OF PROBLEMS, ALTERNATIVES, AND POLICY RECOMMENDATIONS FOR IMPROVING THE QUALITY OF ISLAMIC EDUCATION MANAGEMENT IN THE ERA OF DIGITAL TRANSFORMATION - Nurhayati, Neng; Idris, Ahmad; Marfu, Asep; Fauzi, Anis (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Digital transformation creates fundamental challenges for Islamic education management that require a strategic and comprehensive policy response. This research aims to identify problems in the management of Islamic education in the context of digital transformation, formulate strategic policy alternatives, and produce implementable policy recommendations. Using a qualitative method with a library research approach, the study analyzed primary sources including scientific journals, reference books, and education policy documents published in the period 2022-2025. The data analysis technique uses content analysis with the stages of source identification, theme categorization, critical interpretation, and conceptual synthesis. The results of the study revealed three main dimensions of problems, namely the limitation of technological infrastructure, the gap in human resource competencies, and the lack of adaptive policies. The research formulates alternative policies in the form of developing digital infrastructure through multi-stakeholder cooperation, human resource capacity building programs, and curriculum redesign integrated with Islamic-digital values. The resulting policy recommendations include the development of an integrated digital ecosystem, the transformation of managerial processes, digital competency acceleration programs, the reformulation of adaptive regulations, and sustainable funding models. The significance of the research lies in its contribution in developing a theoretical model of "Digital Islamic Educational Management" that bridges the epistemological gap between tradition and modernity and provides an implementable framework for the sustainable digital transformation of Islamic education